The determinants of counterproductive work behaviour: a concept paper / Dewi Muzalifah Zainal ... [et.al] - Zainal, Dewi Muzalifah; Othman, Nor Azairiah Fatimah; Mustapa, Zuhaina; Abdullah, Jamalunlaili (UiTM Cawangan Johor, 2024)
For the past few years, counterproductive work behaviour (CWB) cases among workforces have been on the rise. Although CWB easily goes unnoticeable in many organizations, absenteeism, sabotage and theft signified CWB at workplaces. Regardless of forms, CWB are harmful to the organization or fellow employees and undermine the goals and interests of a business. As present workplaces see spikes in CWB occurrences, many employers are fearful that their employees are much more likely to engage in any CWB which is why understanding the determinants of CWB is gaining importance. In relation to CWB, The Job Demands-Resources (JD-R) model has been repeatedly used in explaining the well-being and performance of employees in occupational settings. The objective of this paper is to provide an overview of the JD-R model, which incorporates workload as job demand, job control as job resources, job stress as strain and job engagement as motivation with CWB as the behavioural stress reaction. This study adds value to the existing knowledge by developing a conceptual understanding that determinants of CWB at workplace is context-specific from the manufacturing industry lens. To the fact employees are an important asset in today's increasingly competitive business environment, a review of counterproductive behaviour at the workplace is deemed appropriate.